Silencing long non‐coding RNA DLX6‐AS1 or restoring microRNA‐193b‐3p enhances thyroid carcinoma cell autophagy and apoptosis via depressing HOXA1. Issue 19 (12th September 2021) - Feng, Ling; Wang, Ru; Wang, Yifan; Shen, Xixi; Shi, Qian; Lian, Meng; Ma, Hongzhi; Fang, Jugao
Abstract: Long non‐coding RNA DLX6 antisense RNA 1 (DLX6‐AS1) lists a critical position in thyroid carcinoma (TC) development. However, the overall comprehension about DLX6‐AS1, microRNA (miR)‐193b‐3p and homeobox A1 (HOXA1) in TC is not thoroughly enough. Concerning to this, this work is pivoted on DLX6‐AS1/miR‐193b‐3p/HOXA1 axis in TC cell growth and autophagy. TC tissues and adjacent normal thyroid tissues were collected, in which expression of DLX6‐AS1, miR‐193b‐3p and HOXA1 was tested, together with their interactions. TC cells were transfected with DLX6‐AS1/miR‐193b‐3p‐related oligonucleotides or plasmids to test cell growth and autophagy. Tumorigenesis in nude mice was observed. DLX6‐AS1 and HOXA1 were up‐regulated, and miR‐193b‐3p was down‐regulated in TC. Depleted DLX6‐AS1 or restored miR‐193b‐3p disturbed cell growth and promoted autophagy. DLX6‐AS1 targeted miR‐193b‐3p and positively regulated HOXA1. miR‐193b‐3p inhibition mitigated the impaired tumorigenesis induced by down‐regulated DLX6‐AS1. Tumorigenesis in nude mice was consistent with that in cells. It is clear that DLX6‐AS1 depletion hinders TC cell growth and promotes autophagy via up‐regulating miR‐193b‐3p and down‐regulating HOXA1.